1996
DOI: 10.1021/ma9602583
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Flexibility of a Rigid Linear Conjugated Polymer

Abstract: The unusual electronic and optical properties of many electroluminescent and conducting polymers arise from extended conjugation along the polymer backbone, which can also lead to insolubility, aggregation, and gelation. Synthetic efforts to produce an optimal structure require a balance between the persistence length and the effective conjugation length for the successful implementation of these materials in photonic and electronic devices. In this study, we have investigated the solution properties of a grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
116
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 39 publications
12
116
0
Order By: Relevance
“…This is quantified by the calculated end-to-end distances of hR ee = 92 nm in PPE and hR ee i = 42 nm in PTPE, after averaging over 1000 realizations of a 100-unit-long polymer chain. Our simulations for PPE qualitatively reproduce the trends observed experimentally by Swager et al that low molecular weight fractions of this polymer show rigid-rod behavior [50] . On the other hand, PTPE chains show a higher propensity to behave as "wormlike" chains.…”
Section: Equilibrium Ground-state Geometriessupporting
confidence: 87%
“…This is quantified by the calculated end-to-end distances of hR ee = 92 nm in PPE and hR ee i = 42 nm in PTPE, after averaging over 1000 realizations of a 100-unit-long polymer chain. Our simulations for PPE qualitatively reproduce the trends observed experimentally by Swager et al that low molecular weight fractions of this polymer show rigid-rod behavior [50] . On the other hand, PTPE chains show a higher propensity to behave as "wormlike" chains.…”
Section: Equilibrium Ground-state Geometriessupporting
confidence: 87%
“…Dynamic light scattering (DLS) analysis showed that the average length of P1 is 16 nm, a value that corresponds to the typical persistence length of long PPEs. [8] DLS measurements in perfluorodecalin also showed similar length distributions. When P1 was end-capped with 1-bromo-4-tertbutylbenzene, no signals corresponding to the tert-butyl group were observed in the 1 H NMR spectrum, indicating a high degree of polymerization (> 20).…”
supporting
confidence: 53%
“…We have undertaken an experimental determination of C v , closely following the procedure outlined by Cotts et al in [6]. The approach is to use coupled gel permeation chromatography/light scattering [GPC/LS] measurements.…”
Section: Resultsmentioning
confidence: 99%